Eleven undescribed alkaloids from the rhizomes of Sinomenium acutum and their IDO1 and TDO inhibitory activities. (August 2022) - Bi, Ran; Yang, Xin-Ni; Zhou, Hao-Feng; Peng, Li-Yan; Liu, Jiang-Xin; Zhao, Qin-Shi
Abstract: Eleven previously undescribed alkaloids, named sinometumines A-K, along with three known alkaloids, were isolated from the rhizomes of Sinomenium acutum . The chemical structures of these unreported compounds were established using extensive spectroscopic methods (IR, UV, HRESIMS, and NMR), and their absolute configurations were determined by single crystal X-ray diffraction analyses and calculated electronic circular dichroism spectroscopy (ECD). Sinometumine D was the first aporphine-type derived alkaloid inner salt with a rearranged dibenzofuran ring backbone. Sinometumine E was a rare protoberberine-type alkaloid with a complex 6/6/6/6/6/6 hexacyclic skeleton. This was the first report of alkaloids with these two skeletons isolated from S. acutum . All isolates were evaluated for their inhibitory activities against indoleamine 2, 3-dioxygenase 1 (IDO1) and tryptophan 2, 3-dioxygenase (TDO). Lysicamine possessed noteworthy inhibitory activities as an IDO1/TDO dual inhibitor with IC50 values of 6.22 ± 0.26  μ M and 23.76 ± 2.93  μ M, respectively, and liriodenine revealed moderate dual inhibition with IC50 values of 31.65 ± 4.44  μ M and 15.64 ± 0.26  μ M. The intermolecular interactions and binding modes between lysicamine and IDO1/TDO were elaborated by molecular docking studies. Graphical abstract: Eleven undescribed alkaloids were isolated and identified from the rhizomes of S. acutum, including two racemates. Sinometumine D was the first aporphine-type derived alkaloid inner salt with a rearranged dibenzofuran ring backbone. Sinometumine E was a rare protoberberine-type alkaloid with a complex 6/6/6/6/6/6 hexacyclic skeleton. This was the first report of alkaloids with these two skeletons isolated from S. acutum . Image 1 Highlights: Eleven undescribed alkaloids were isolated from the rhizomes of Sinomenium acutum. Two racemates were separated by chiral HPLC. Lysicamine showed noteworthy inhibitory activities against IDO1 and TDO. The potential mechanism was explored using molecular docking.